Decision to Consume Halal Food Products in Solo - Pancasari, Retno Rahayuningsih (Indonesian Journal of Banking and Financial Technology, 2024)
Market demand for halal food and beverage products is increasing, creating great business opportunities. This study aims to evaluate the impact of halal product knowledge, halal awareness, and religiosity on k haulinerlal purchasing decisions. Using interval quantitative data from questionnaires with Proportional Random Sampling samples, the analysis was carried out using the Partial Least Square (PLS) method in Structural Equation Modeling (SEM), focusing on components or variants. The results of the analysis show that halal product knowledge has a positive and significant effect on purchasing decisions, meaning that the higher the consumer's knowledge of halal products, the more likely they are to make a purchase. In addition, religiosity is also proven to have a positive and significant effect on purchasing decisions, indicating that religious values ​​influence consumer behavior in choosing halal products. Halal awareness, which includes consumer awareness and attention to the halalness of products, also shows a significant positive effect.